Assessment of the Tribological Performance of Bio-Based Lubricants Using Analysis of Variance - Szewczyk, Marek; Szwajka, Krzysztof (Advances in Mechanical and Materials Engineering, 2023)
The purpose of this article is to determine the coefficient of friction of the DC04 steel sheet using a specially designed flat die strip drawing test. Four different bio-based lubricants, edible (sunflower and rape-seed) and non-edible (Karanja and Moringa) were used in the study. The experiments were carried out for different values of contact pressure. The as‐received specimens were pre‐strained with strains of 7, 14, and 21%. The values of the coefficient of friction as a ratio of the friction force to the normal force were determined. The influence of viscosity of lubricant and contact pressure on the value of coefficient of friction has been investigated using ANOVA. A tendency to decrease in the coefficient of friction with increasing the contact pressure was observed. Significance results obtained after the ANOVA analysis confirmed the influence of normal pressure and oil viscosity on the value of the coefficient of friction. At the same time, the hypothesis about the influence of the sheet pre-straining on the value of the friction coefficient was not confirmed by the significant interactions.